Dialogue in the Sunnah - امهدرس امدكخِر وطىد ؤرزا آغا ؤرزا آغا (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This research entitled:" The Dialogue in the Prophetic Sunnah". It denotes to the importance of dialogue in people's life. It is the door of civilization to instill stability in the community. Islam has called on dialogue and emphasized on its significant. Likewise, Islam rejected discrimination between people. The prophet Muhammad –peace be upon him- used the dialogue as a dispensable tool to call people to embrace Islam. The main aim of this research is to give a true image of dialogue in the prophetic sunnah. The research illustrates the definition of dialogue linguistically and terminology, then, the attitudes and aims of dialogue, and the ways of dialogue in the prophetic Sunnah with non-Muslims, the companions of the prophet. Eventually, the research shows the most important results.